The Right to Science Then and Now - Porsdam, Helle; Porsdam Mann, Sebastian (Social Sciences, 2021)
Leading academics, civil servants, lawyers, policymakers, and civil society representatives reflect on the powerful-but-neglected human right to science. This will appeal to anyone interested in how this right is pertinent to numerous issues at the intersection of science and society. This title is also available as Open Access on Cambridge Core.